PROCESS MANAGEMENT SYSTEMS IN THE BUSINESS-ORIENTED MODEL OF ENTERPRISE DEVELOPMENT - Valentyna A. Pavlova (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku, 2022)
The article examines the business processes of modern entrepreneurship. Based on the content analysis of approaches to their definition, management of their implementation, description in various spheres of economic activity, the need for automation and optimization, a conceptual pattern of business processes is proposed. According to the concept, the input and output criteria of business processes, their structure and sequence of operations and the interaction of units depending on the field of activity are chosen. Fact-checking of statistical information on the share of various types of economic activity in the formation of the gross domestic product was carried out, which allows us to determine their socio-economic significance and highlight the basis for the formation of the structure of business processes. Information on the results of a survey on the state and needs of business in wartime conditions is presented, ways of adapting entrepreneurship to the challenges of wartime and preserving and developing business are considered. The importance of the business team in achieving strategic and tactical goals is highlighted. The criteria by which the business team is evaluated are highlighted. , among them: responsibility for the quality of execution, distribution of areas of responsibility, highquality interaction, speed of adaptation of internal capabilities to external challenges, business climate of the external environment. It was established that the process-oriented model requires the presence of interconnected actions, the implementation of which ensures the achievement of the final result. To ensure business effectiveness, an appropriate algorithm for the implementation of actions and procedures is selected based on the structuring of business processes. The need to introduce a process approach in the management of a business entity and individual processes of its activity, where one of the tools is the selection of their management systems, is proven. The cause-and-effect relationship between the structure of business processes and the choice of an appropriate system for managing them and resources and influencing factors according to the Ishikawa diagram is determined, which will prevent risks and the occurrence of undesirable causes that prevent the achievement of business goals. The evolution of management and information technologies is considered, the stages of functionality of business process management systems in which business functions are automated are given. The characteristics of the MRP, MRP II, ERP, ERP II systems and their effectiveness for managing the processes of the business entity are given. Trends in the development of ERP systems related to the improvement of resource planning, inventory and production process management modules and the introduction of supply chain management and customer relationship management modules are highlighted. The introduction of digital technologies into the business processes of business entities allows the business to adapt to the uncertain conditions of the external environment.